Medial prefrontal cortex suppresses reward-seeking behavior with risk of punishment by reducing sensitivity to reward - Nishio, Monami; Kondo, Masashi; Yoshida, Eriko; Matsuzaki, Masanori (Frontiers in Neuroscience, 2024)
Reward-seeking behavior is frequently associated with risk of punishment. There are two types of punishment: positive, resulting in an unpleasant outcome, and negative, resulting in omission of a reinforcing outcome. Although the medial prefrontal cortex (mPFC) is important in avoiding punishment, whether it is important for avoiding both positive and negative punishment and how it contributes to such avoidance are not clear. In this study, we trained male mice to perform decisionmaking tasks under the risks of positive (air-puff stimulus) and negative (reward omission) punishment. We found that pharmacological inactivation of mPFC enhanced the reward-seeking choice under the risk of positive, but not negative, punishment. In reinforcement learning models, this behavioral change was well-explained by hypersensitivity to the reward, rather than a decrease in the strength of aversion to punishment. Our results suggest that mPFC suppresses reward-seeking behavior by reducing sensitivity to reward under the risk of positive punishment.